Luigi Ferdinando Marsigli and the Mappa Metallographica: Graphic Creativity and Scientific Measurement (diségno, 2020)
The Mappa Metallographica (45.5 x 70.5 cm) is part ofLa Hongrie et le Danube, a collection of twenty-sevencartographic tables drafted over a period of fifteenyears to illustrate the orography, hydrography and metallurgy of the Hungarian stretch of the Danube [1]. (read more)